Perbedaan Mekanisme Koping Penderita Diabetes Mellitus dengan Ulkus dan Tanpa Ulkus Diabetikum - Rahmawati, Desta Opchera Dina; Isworo, Atyanti; Sari, Yunita (Prodi Keperawatan Purwokerto, 2025)
Background: Diabetes mellitus is a long-term disease that causes alterations in lifestyle, influences physical, psychological health, and causes many complications, including diabetic ulcers. The alteration of life in diabetic patients that was caused by diabetes mellitus, or diabetic ulcer, could be a stressor for patients. The coping mechanism was formed as an adaptation to that stressor. Coping mechanisms in patients could be problem-focused coping and emotion-focused coping. Objective: This research aimed to determine the differences in coping mechanisms between diabetic patients with and without diabetic ulcers at RSUD Margono Soekarjo Purwokerto. Methods: This research was a comparative research design. The sampling technique was purposive sampling. There were 49 respondents, 18 patients with diabetic ulcers and 31 patients without diabetic ulcers. Data was collected using the COAP questionnaire and analyzed using the Chi-square test. Results: There was no difference in coping mechanisms between diabetic patients with and without diabetic ulcers (p=0.443). Emotion-focused coping was the most used coping mechanism among subjects with and without diabetic ulcers, and the coping mechanism of diabetic patients with and without ulcers was not different. The most important aspects of emotion-focused coping in respondents with and without diabetic ulcers were oriented to religion, which caused positive emotion and mental endurance to face the problem. Conclusion: Coping mechanisms between diabetic patients with and without diabetic ulcers were commonly performed emotion-focused coping.